ANALYSIS OF SOCIAL MEDIA IMPACT AND ITS BENEFIT ON THE DEVELOPMENT OF SMALL MEDIUM ENTERPRISES IN MANADO - Rajenra, I Dewa Made; Massie, James D.D; Rumokoy, Farlane S. (Universitas Sam Ratulangi, 2017)
Abstract: Nowadays, social media is growing so rapidly and almost everyone in the world has account social media. Ranging from children to adults use social media to communicate with other people in daily life. The awareness for SMEs in Manado to take advantage in using social media already existed and continues to increase day by day. This research was held in Manado as a developing city in Indonesia with SMEs that has Social media as the samples. Qualitative research is deployed to define the nature SMEs in Manado. The results of this research show the social media can increase the sales, revenue, brand awareness and the number of customer of SMEs in Manado. The problem that SMEs faced in using social media in Manado is the SMEs cannot respond to all customers who want to wonder about their products on social media. For the government, it is necessary to provide good connection internet especially not only in urban but rather in rural areas, because there are still many in rural areas who haven't connected with the internet , with the internet people can access social media which can help the SMES in rural areas to develop their business.Keywords: small medium enterprise, social media impact and its benefit, problem in using social media